Global Bifurcation of Positive Solutions of Asymptotically Linear Elliptic Problems - Ruyun Ma; Yanqiong Lu; Ruipeng Chen (Abstract and Applied Analysis)
We are concerned with determining values of λ, for which there exist positive solutions of the nonlinear elliptic problem -Δu=λa(x)f(u)  in  Ω, ∂u/∂n+b(x)g(u)=0  on  ∂Ω. The proof of our main results is based upon unilateral global bifurcation theorem of López-Gómez.